Gerbils - Hearne, Tina. (Vero Beach, FL : Rourke Publications, 1989)
Examines the different varieties of gerbils and describes how they may be housed, exercised, handled, fed, cleaned, and bred.
Includes index.
6.3
3-6
Keywords: Gerbils as pets -- Juvenile literature; Gerbils; Gerbils; Gerbils